Benefit–harm analysis of azithromycin for the prevention of acute exacerbations of chronic obstructive pulmonary disease. Issue 11 (26th November 2021) - Ahmadian, Safa; Sin, Don D; Lynd, Larry; Harrison, Mark; Sadatsafavi, Mohsen
Abstract : Background: Low-dose oral azithromycin therapy is recommended as a preventive treatment for acute exacerbations of COPD. However, the overall benefit–harm balance of this treatment has not been well studied. Methods: A probabilistic Markov model of COPD was created to simulate the course of COPD over 20 years. The model was populated with evidence from the literature and dedicated data analysis. The benefit of azithromycin was modelled as a reduction in exacerbation rates. Adverse events, including cardiovascular events, hearing loss, gastrointestinal symptoms and antimicrobial resistance (leading to a gradual decline in the effectiveness of azithromycin), were considered. All outcomes were assigned a health-related utility weight to estimate the overall net change in the quality-adjusted life year (QALY) associated with the use of azithromycin. Results: In patients with a positive exacerbation history, azithromycin resulted in a net QALY gain of 17.9 per 100 patients (99.8% probability of expected QALY gain) over 20 years. The net benefit increased to 21.8 QALYs per 100 patients (99.9% probability of expected QALY gain) among the 'frequent exacerbator' subgroup. Azithromycin was not net beneficial among those without any moderate/severe exacerbations in the previous year. Findings were robust against series of sensitivity, scenario and threshold analyses. Conclusions: Long-term therapy with azithromycin confers a net benefit to ex-smoker patients with COPD with a recent history of exacerbations and an even larger benefit to those who are frequent exacerbators.